Maternal AED Treatment and Neonatal Behavior - J Gordon Millichap (Pediatric Neurology Briefs, 1996)
The relationship between antiepileptic drug (AED) treatment during pregnancy, neurobehavior of the neonate, and the neurological outcome in later life of 40 children exposed in utero to a single AED (phenobarbital, phenytoin, valproic acid) was studied at Children’s Hospital, Virchow Klinikum of the Humboldt University Berlin: Institute of Toxicology and Embryopharmacology, Free University Berlin; and Department of Neuropediatrics, Children’s Hospital, University of Heidelberg, Germany.